2011
DOI: 10.1007/978-3-642-24855-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for Prostate Cancer Prognosis Using a Novel Two-Step Cluster Analysis

Abstract: Abstract. Prognosis of Prostate cancer is challenging due to incomplete assessment by clinical variables such as Gleason score, metastasis stage, surgical margin status, seminal vesicle invasion status and preoperative prostate-specific antigen level. The whole-genome gene expression assay provides us with opportunities to identify molecular indicators for predicting disease outcomes. However, cell composition heterogeneity of the tissue samples usually generates inconsistent results for cancer profile studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The two exclusive features make CC analysis better than traditional gene expression analyses. In a previous study [17] we compared the CC analysis model with traditional gene differential expression analyses such as by SAM and LIMMA. The simulation results showed that the new model outperformed the traditional gene differential expression analyses in terms of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two exclusive features make CC analysis better than traditional gene expression analyses. In a previous study [17] we compared the CC analysis model with traditional gene differential expression analyses such as by SAM and LIMMA. The simulation results showed that the new model outperformed the traditional gene differential expression analyses in terms of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation results showed that the new model outperformed the traditional gene differential expression analyses in terms of sensitivity and specificity. In addition, when these methods were applied to prostate cancer data, the CC analysis can identify genes that are significantly enriched or associated with prostate cancer related pathways such as the wnt signaling pathway, ECM-receptor interaction, focal adhesion and TGF- β signaling pathway [17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations